2007
DOI: 10.1177/039463200702000104
|View full text |Cite
|
Sign up to set email alerts
|

Reparixin, a Specific Interleukin-8 Inhibitor, Has No Effects on Inflammation during Endotoxemia

Abstract: Reparixin antagonizes interleukin-8 (IL-8) on the level of signal transduction in vitro. We hypothesized that IL-8 mediates some of the reactions occurring during acute inflammation and specifically that IL-8 may be a mediator of endotoxin induced neutrophilia. We therefore tested the effects of reparixin on humoral and cellular parameters in LPS-induced acute systemic inflammation. The study is a randomized (3:2 active:placebo), double-blind, placebo-controlled parallel group trial. Twenty healthy male volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…TF-mRNA expression of circulating leukocytes was at or below the detection limit of 37.5 amplification cycles in all subjects at baseline (Table 1). Similar to previous trials [18], LPS infusion caused a 14-19 fold increase in TF-mRNA levels after 4 h [19 fold increase (CI: [14][15][16][17][18][19][20][21][22][23][24][25] in Africans vs. 14-fold (CI: 9-18) in Caucasians; P > 0.05 between groups; Fig. 3B].…”
Section: Effect Of Lps On Leukocyte Tf-mrna Expressionsupporting
confidence: 84%
See 1 more Smart Citation
“…TF-mRNA expression of circulating leukocytes was at or below the detection limit of 37.5 amplification cycles in all subjects at baseline (Table 1). Similar to previous trials [18], LPS infusion caused a 14-19 fold increase in TF-mRNA levels after 4 h [19 fold increase (CI: [14][15][16][17][18][19][20][21][22][23][24][25] in Africans vs. 14-fold (CI: 9-18) in Caucasians; P > 0.05 between groups; Fig. 3B].…”
Section: Effect Of Lps On Leukocyte Tf-mrna Expressionsupporting
confidence: 84%
“…During human endotoxemia, neither blockade of tumor necrosis factor (TNF) [22], interleukin‐6 (IL‐6) [23] or IL‐8 [24] alters coagulation. Both groups showed a similar inflammatory response as measured by TNF and IL‐6 [9], which suggests that these factors do not contribute to the observed racial differences in coagulation, and induction of similar TF mRNA levels indicates a preserved general response pattern to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL2 is the mouse homologue of human IL-8, a potent neutrophil chemoattractant that is consistently associated with neutrophilic inflammation during asthma exacerbation (45,46). IL-8 antagonists have been developed; however, in early clinical trials, blockade of IL-8 by itself has no significant effect on inflammation (47). Thus, blockade of neutrophil-derived proteases, such as DPPI, may present an alternative way to reduce chemoattractant levels without compromising the host defense.…”
Section: Discussionmentioning
confidence: 99%
“…Repertaxin was originally developed to block CXCL8 activity, and thus reduce tissue damage after myocardial infarction or stroke 210 . A phase I clinical trial has demonstrated that repertaxin is well tolerated in healthy volunteers 211 . Further clinical trials are needed to determine the safety and efficacy of repertaxin in combination with current immunotherapies in patients with cancer.…”
Section: Chemokines and Cancer Immunotherapymentioning
confidence: 99%